Log content extraction engine based on ontology for the purpose of a posteriori access control. (2nd February 2015) - Azkia, Hanieh; Cuppens–Boulahia, Nora; Cuppens, Frédéric; Coatrieux, Gouenou
In some complex information systems, users do not undergo untimely access controls. Generally, whenever they perform an action, this action is logged by the target system. Based on these log files, a security control called a posteriori access control is made afterwards. The logged data can be recorded in different formats (Syslog, W3C extend log, specific domain log standard like IHE–ATNA, etc.). An a posteriori security control framework requires a log filtering engine which extracts useful information regardless of the log format used. In this paper, we define and enforce this extraction function by building an ontology model of logs. This logs ontology is queried to check the compliance of actions performed by the users of the considered system with its access control policy (violations, anomalies, fulfilments, etc.). We show how the a posteriori security controls are made effective and how security decisions are made easier based on this extraction function.